Public Service Quality at the Bikomi Nilulat Sub-district Office North Central Timor Regency - Yohanes Handrianus Laka (International Research and Development for Human Beings (IRDH), 2026)
Law Number 25 of 2009 concerning Public Services establishes principles of good governance as a measure of government effectiveness. Public service is a strategic policy issue, reflecting organizational performance and requiring quality improvement to protect citizens’ rights. According to Herbert Simon, organizations are cooperative systems in which each participant has defined roles and obligations. In line with the Regulation of the Minister of State Apparatus Empowerment Number 63 of 2003, public services are provided by central and regional agencies, as well as state-owned enterprises, to meet community needs and implement legal provisions. Examples include administrative services such as identity cards, family cards, and certificates. This study employs a qualitative descriptive approach to analyze public service performance, focusing on how organizational factors influence effectiveness. Data are examined to describe phenomena and identify solutions to emerging problems, highlighting that the performance of public organizations is shaped by multiple determinants. The implementation of Standard Operating Procedures (SOPs) at the Bikomi Nilulat Sub-district Office, North Central Regency, has not been fully optimal or systematic, particularly in ensuring clarity, coordination, and control of operational activities. While the overall quality of public services is considered good, shortcomings remain in employee ethics, which cause discomfort for service users. Moreover, the Sub-district Head has not shown strong progressiveness in supervising and evaluating compliance with regional regulations and ministerial guidelines on public service standards, resulting in gaps between policy expectations and actual service delivery.